KEPEMIMPINAN KULTURAL MELAYU DI WILAYAH SINGAPURA, JOHOR, KEPRI (SIJORI) DIANTARA ARTIFICIAL INTELLIGENCE DAN TRANSFORMASI DIGITAL ERA - Chartady, Rachmad; Alamsyahbana, Muhammad Isa; Armansyah, Armansyah; Indriaty, Novica (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This paper aims to explore the role of cultural leadership in the SIJORI region (Singapore, Johor, and the Riau Archipelago) in leveraging artificial intelligence (AI) and digital transformation to preserve and enrich local cultural identity. As globalization and technological advancements accelerate, cultural leaders in SIJORI face the challenge of upholding cultural values while embracing digital innovation. This paper highlights the core elements of cultural leadership—cultural awareness, empathy, adaptability, inclusive communication, cultural innovation, and community empowerment—and examines how these elements can be strengthened through the use of AI and digital platforms. Under culturally aware leadership, technology can be harnessed to foster cross-cultural collaboration, preserve local heritage, and drive innovation within cultural practices. This study underscores the importance of adaptive cultural leadership in digital strategies, aiming to build communities that are deeply rooted in cultural identity yet prepared to navigate the challenges of the continually evolving digital age. Keywords: Cultural Leadreship, SIJORI Region, Artificail Intelligence, Digital Transformation, Cross-Cultural Collaboration Abstrak: Makalah ini bertujuan untuk mengeksplorasi peran kepemimpinan budaya di wilayah SIJORI (Singapura, Johor, dan Kepulauan Riau) dalam memanfaatkan kecerdasan buatan (AI) dan transformasi digital untuk melestarikan dan memperkaya identitas budaya lokal. Seiring percepatan globalisasi dan kemajuan teknologi, para pemimpin budaya di SIJORI menghadapi tantangan untuk menjunjung tinggi nilai-nilai budaya sambil merangkul inovasi digital. Makalah ini menyoroti elemen inti kepemimpinan budaya—kesadaran budaya, empati, adaptabilitas, komunikasi inklusif, inovasi budaya, dan pemberdayaan masyarakat—dan meneliti bagaimana elemen-elemen ini dapat diperkuat melalui penggunaan AI dan platform digital. Di bawah kepemimpinan yang sadar budaya, teknologi dapat dimanfaatkan untuk mendorong kolaborasi lintas budaya, melestarikan warisan lokal, dan mendorong inovasi dalam praktik budaya. Studi ini menggarisbawahi pentingnya kepemimpinan budaya adaptif dalam strategi digital, yang bertujuan untuk membangun komunitas yang berakar kuat dalam identitas budaya namun siap menghadapi tantangan era digital yang terus berkembang. Kata Kunci: Kepemimpinan Budaya, Wilayah SIJORI, Kecerdasan Buatan, Transformasi Digital, Kolaborasi Lintas Budaya